Intraoperative colonoscopy in patients with colorectal cancer: Review of recent developments. Issue 6 (28th April 2016) - Kawai, Kazushige; Iida, Yuuki; Ishihara, Soichiro; Yamaguchi, Hironori; Nozawa, Hiroaki; Hata, Keisuke; Kiyomatsu, Tomomichi; Tanaka, Toshiaki; Nishikawa, Takeshi; Yasuda, Koji; Otani, Kensuke; Murono, Koji; et al.
Abstract : The use of intraoperative colonoscopy has increased alongside progress in the development of colonoscopy‐associated devices and techniques, including the colonoscope itself. In the present review, we focus on four circumstances in which intraoperative colonoscopy is beneficial to colorectal surgery: (i) intraoperative determination of a tumor's location; (ii) observation of the proximal colon in cases of obstructive colorectal cancer; (iii) confirmation of the integrity of anastomosis; and (iv) novel surgical techniques that combine laparoscopic and endoscopic surgery. In light of the findings of our review, a combination of colonoscopy and surgery—especially laparoscopic surgery—is expected to facilitate the optimal handling of a variety of colorectal tumors, ranging from benign cases to advanced and obstructive cases.